The meaning of genocide and terror in cognitive tourism - Tanaś, Sławoj (Turyzm/Tourism, 2013)
The article considers the influence of acts of terror and war crimes on both the development of tourism, or a lack of it. Terrorist attacks, the victims of which are tourists as well as local citizens, constrain or completely prevent tourism development. Terrorism is then a barrier to the development of the tourism economy. With time, however, memory of the crime and its victims, due to documentation and commemoration, may become an impulse to organize spaces which will be included in tourism.